2018
DOI: 10.1139/cjpp-2018-0275
|View full text |Cite
|
Sign up to set email alerts
|

Doxorubicin induces de novo expression of N-terminal-truncated matrix metalloproteinase-2 in cardiac myocytes

Abstract: Anthracyclines, such as doxorubicin, are commonly prescribed antineoplastic agents that cause irreversible cardiac injury. Doxorubicin cardiotoxicity is initiated by increased oxidative stress in cardiomyocytes. Oxidative stress enhances intracellular matrix metalloproteinase-2 (MMP-2) by direct activation of its full-length isoform and (or) de novo expression of an N-terminal-truncated isoform (NTT-MMP-2). As MMP-2 is localized to the sarcomere, we tested whether doxorubicin activates intracellular MMP-2 in n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 43 publications
2
10
0
3
Order By: Relevance
“…For instance, a study by Mohammed et al investigated the impact of a sublethal concentration of doxorubicin on several cancer cell lines, revealing that sublethal concentrations enhances cell migration and invasion through SFK activation in both non‐invasive and invasive cancer cell lines, including U2OS 23 . Furthermore, doxorubicin has been reported to increase the expression of MMP‐2 and MMP‐9 in cardiac myocytes 11,24 . These findings align with the study by Mohammed et al, as a sublethal concentration of doxorubicin activates SFKs, augmenting the expression of MMP‐2, and consequently, enhancing cell migration 23 …”
Section: Introductionsupporting
confidence: 71%
“…For instance, a study by Mohammed et al investigated the impact of a sublethal concentration of doxorubicin on several cancer cell lines, revealing that sublethal concentrations enhances cell migration and invasion through SFK activation in both non‐invasive and invasive cancer cell lines, including U2OS 23 . Furthermore, doxorubicin has been reported to increase the expression of MMP‐2 and MMP‐9 in cardiac myocytes 11,24 . These findings align with the study by Mohammed et al, as a sublethal concentration of doxorubicin activates SFKs, augmenting the expression of MMP‐2, and consequently, enhancing cell migration 23 …”
Section: Introductionsupporting
confidence: 71%
“…In a DOX-induced cardiotoxicity study, Polegato et al (2015) showed that DOX partially increased MMP-2 activity. Chan et al (2018) reported that DOX increased MMP-2 activity and levels in cardiomyocytes. In their DOX-induced toxicity study performed using Western blotting, they also found that DOX increased MMP-2 levels and decreased TIMP2 levels.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, MMP-9 overexpression has also been correlated with poor prognosis in colon, gastric, lung, and pancreatic cancers [83]. Dox has been reported to induce MMP-2 and MMP-9 in cardiac myocytes via MAP kinase pathway as well as through AP-1 pathway in oxidative stress [84,85]. MMP-14 is a crucial player in active cellular invasion.…”
Section: Discussionmentioning
confidence: 99%